2016
DOI: 10.1098/rsos.150670
|View full text |Cite
|
Sign up to set email alerts
|

Assessing recognition memory using confidence ratings and response times

Abstract: Classification of stimuli into categories (such as ‘old’ and ‘new’ in tests of recognition memory or ‘present’ versus ‘absent’ in signal detection tasks) requires the mapping of internal signals to discrete responses. Introspective judgements about a given choice response are regularly employed in research, legal and clinical settings in an effort to measure the signal that is thought to be the basis of the classification decision. Correlations between introspective judgements and task performance suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 61 publications
9
75
0
Order By: Relevance
“…Regarding the interaction, the data were insensitive, BF 01 ϭ 1.31; F (1,59) ϭ 3.11, p ϭ .083, G 2 ϭ .004. For recognition speed, taken as a measure of recognition confidence (Weidemann & Kahana, 2016), RTs did not differ for pseudowords previously presented on MP8 (M ϭ 759 ms) or MP4 (M ϭ 760 ms, difference: M ϭ 1.0 ms, 95% CI [Ϫ10.9, 15.2], d ϭ 0.04). There is strong support for the null hypothesis, BF 01 ϭ 11.12; F (1,59) Ͻ 1; see Figure 5D.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the interaction, the data were insensitive, BF 01 ϭ 1.31; F (1,59) ϭ 3.11, p ϭ .083, G 2 ϭ .004. For recognition speed, taken as a measure of recognition confidence (Weidemann & Kahana, 2016), RTs did not differ for pseudowords previously presented on MP8 (M ϭ 759 ms) or MP4 (M ϭ 760 ms, difference: M ϭ 1.0 ms, 95% CI [Ϫ10.9, 15.2], d ϭ 0.04). There is strong support for the null hypothesis, BF 01 ϭ 11.12; F (1,59) Ͻ 1; see Figure 5D.…”
Section: Resultsmentioning
confidence: 99%
“…Given the surprising absence of auditory entrainment on recognition memory accuracy, we turn to the speed of recognition responses which has previously been linked to the confidence of memory judgments (Weidemann & Kahana, 2016). Perhaps, RT provides a more fine grained measure than accuracy rates.…”
Section: Resultsmentioning
confidence: 99%
“…Effects of uncertainty about the solution could become apparent in the period after space key press, when the idea needs to be phrased and evaluated. Note that as uncertainty about the solution increases, reaction times typically also increase 43 . However, here we did not observe a relationship between creativity and the time it took participants to start submitting their solution, nor did we find a relation between reaction times and mid frontal theta changes.…”
Section: Discussionmentioning
confidence: 99%
“…Reaction times (RT) were also analyzed to control for any differences in task difficulty as reflected by the speed of memory task performance 101 due to emotion. Recently, it has been also indicated that reaction times provide similar information to explicit ratings of memory confidence in their ability to quantify recognition memory decisions 102 . We performed rm ANOVA with emotion (3 levels: disgust, fear, neutral), novelty (2 levels: old, new) and correctness (2 levels: correct, incorrect) as withinsubject factors.…”
Section: Behavioral Data Analysismentioning
confidence: 99%